Key issues in WTO dispute settlement the first ten years - Yerxa, Rufus H.; Wilson, Bruce (Cambridge University Press, 2005)
This book examines aspects of the operation of the WTO dispute settlement system during the first ten years of the WTO. It covers a representative cross-section of the issues and situations WTO Members have dealt with under the Dispute Settlement Understanding. The book is unique in that it includes contributions from virtually the entire gamut of actors involved in the day-to-day operation of the WTO dispute settlement system: Member government representatives, private lawyers who litigate on behalf of Member governments in the system, Appellate Body members, Appellate Body Secretariat staff, and WTO Secretariat staff. It also includes contributions from several academics who closely follow and carefully scrutinize all that goes on within the system. It therefore provides fascinating insights into how the system has operated in practice, and how the lessons of the first decade can be applied to make the system even more successful in the years to come
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: World Trade Organization; Recht; Arbitration (International law); Foreign trade regulation; Tariff / Law and legislation; Streiterledigung